Effect of Phosphogypsum Addition on Methane Yield in Biogas and Digestate Properties During Anaerobic Digestion - Chubur V.; Chernysh Y.; Ferchau E.; Zaffar N. (Журнал інженерних наук)
The study discussed the use of phosphogypsum by-product waste in anaerobic digestion processes. Besides the production of biogas from plant substrate with the addition of phosphogypsum, the focus was placed on the enrichment of digestate with phosphogypsum as a mineral additive to increase the concentration of valuable macro-and microelements. The component composition of the obtained digestates was analyzed, and opportunities for additional research were determined. Research on the use of mineral additives in anaerobic digestion is considered promising. Phosphogypsum favors the quality of digestate as an organic mineral fertilizer with a higher content of mineral components. Furthermore, the contribution of phosphogypsum to plant substrate to achieve higher biogas production is not apparent, but with an impact on the component composition of biogas; however, there is an opportunity to consider the potential benefits of using the additive with another type of substrate waste for the anaerobic digestion process.